Competence of personnel is a base of strategic development of company - Nurguzhin, M.R.; Amirova, A.N. (Recent Contributions to Physics, 2013)
The problems and ways of solutions on selection and training of competent fit technical personnel to implement of space projects of the Republic of Kazakhstan are considered in this article. It is shown that fulfillment of tasks in the frame of mission and position of the JSC «NC «Kazakhstan Gharysh Sapary» is special role for training of professionally trained engineering and technical specialists and high level managers. Relevance of the training of high qualified specialists in the field of development, designing and creation of space-system engineering is dictated by the implementation of number huge investment projects and activities aimed on creation of basic space objects of the Republic of Kazakhstan. Special consideration is given to implementation of pilot project of the JSC «NC «Kazakhstan Gharysh Sapary» and it will give the uniform methodology and instruments to determine the personnel competence and evaluation under its contribution into the implementation of development strategy of the JSC «NC «Kazakhstan Gharysh Sapary», great impulse for personnel development and its motivation aimed on specific result. Introduction process of evaluation of personnel competence allows to improve the system of staff policy in the JSC «NC «Kazakhstan Gharysh Sapary» and also activities with candidate pool which gives the opportunity to meet their demand in specialists with the competence in the frame of research specified in our list required for high qualified personnel under current conditions. In the result of research it is detected that the formation of competent staff on the base of competence evaluation results and further purposeful development of personnel will assist the business improvement of Company and space industry as well.